ISO 9002 quality system and its impacts on a pharmaceutical distribution company : a case study of Zuellig Pharma Ltd. - Jariya Nichai; Do Ba Khang; Johri, Lalit M.; Paul, Himangshu; Zuellig Pharma Ltd., Thailand (Pathum Thani, Thailand : Asian Institute of Technology, 2000)
Quality Management System presently has become a tool for competitive advantage in business section. ISO 9000 series is one of Quality Management System, which many companies apply widely. Zuellig Pharma Ltd, a pharmaceutical distributor, is also one of many companies that decided to embark to ISO 9000 system. Working on ISO 9000 Project in order to achieve the company's objective within a year without the external consultant had given the lessons and good experience. Though, the company has already been certified by ISO 9002 Quality Management System, but the working on project did not stop when getting certified. The system still keeps continued, together with the new finding for development. The research on the impacts after ISO registration for Zuellig Pharma will help to discover for the new finding and bring to the step of development for continuos improvement program. The study does cover not only the perception and attitude of customers and Principals, but also ZPL staff as they are a part of the success in working on the project.
A research study submitted in partial fulfillment of the requirements for the degree of Master in Business Administration (Executive MBA Program)
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2000
Keywords: ISO 9000 Series Standards; Pharmaceutical industry -- Quality control -- Thailand